The End-Organ Impairment in Liver Cirrhosis: Appointments for Critical Care. (16th May 2012) - Figueiredo, Antonio; Romero-Bermejo, Francisco; Perdigoto, Rui; Marcelino, Paulo
Abstract : Liver cirrhosis (LC) can lead to a clinical state of liver failure, which can exacerbate through the course of the disease. New therapies aimed to control the diverse etiologies are now more effective, although the disease may result in advanced stages of liver failure, where liver transplantation (LT) remains the most effective treatment. The extended lifespan of these patients and the extended possibilities of liver support devices make their admission to an intensive care unit (ICU) more probable. In this paper the LC is approached from the point of view of the pathophysiological alterations present in LC patients previous to ICU admission, particularly cardiovascular, but also renal, coagulopathic, and encephalopathic. Infections and available liver detoxifications devices also deserve mentioning. We intend to contribute towards ICU physician readiness to the care for this particular type of patients, possibly in dedicated ICUs.